Mots en conflit. Le rôle de l’oxymore dans le discours médiatique - Dyoniziak, Jolanta (Neophilologica, 2015)
The article is situated in the area of communication research and is related to the phenomenon of media coverage. The author analyses the pragmatic potential of press-based denominative units containing oxymorons. The language material derives from French and Polish political press available electronically according to chosen titles. The discussed problem seems essential for research on media strategy, which is responsible for creating information in contemporary societies. It influences cognitive processes by the paradox of comparing contrasting concepts, enables realization of several crucial ranges of media strategy, which are discussed in the article.